A SUPERBUG (METHICILLIN RESISTANT STAPHYLOCOCCUS AUERUS) IN HUMAN - Sumaira Kanwal; Muhammad Akram; Abid Rashid et al. (Journal of University Medical & Dental College, 2014)
ABSTRACT OBJECTIVE: To study incidence the (MRSA) methicillin resistance staphylococcus aureus in various surgical pathologies. DESIGN: Non probability random sampling. PLACE & DURATION OF STUDY: Study was conducted in Allied Hospital & Independent Hospital from March 2003 to Feb 2004. RESULTS: Total 340 randomly collected samples from patient were analysed for presence of MRSA. Of 340 samples 162 (47.53) were positive for S. aureus, of these 52.64 % (n = 85) were MRSA while resistance 47.5 (n = 77) were found to MSSA. Hospital based analysis showed that 58.64 (n = 95) and 41.51 (n = 67) percent. S. aureus respectively from AHF & IMC Hospital. CONCLUSION: Incidence of MRSA is acutely high in our hospitals. The highest no of MRSA were isolated from wound samples.